A STYLISTICS ANALYSIS IN FARHAT ABBAS’ TWITTER CRITICISM TO AHMAD DHANI ON ABDUL QODIR JAELANI’S TOL JOGORAWI ACCIDENT CASE - YUNITA, LULUK TRISNA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keyword: stylistics, types of stylistics in sentence structure scope, types of stylistics in directing meaning (figurative language) scope, twitter criticism. This study deals with the style used by Farhat Abbas in his twitter. The writer chooses this topic because the writer sees types of style used by Farhat Abbas in his twitter. This study is to answer the questions: 1a) what types of style are used by Farhat Abbas in sentence structure scope?, 1b) what types of are style used by Farhat Abbas in directing meaning (figurative language) scope?, and 2) what is the possible reason of Farhat Abbas to use certain style in twitter criticism toward Ahmad Dhani?. The writer used qualitative approach to analyze the data. Research design was document analysis. The data is text from Farhat Abbas’s twitter taken from www.twitter.com. In this case, the writer only focused on Farhat Abbas’ commentto Ahmad Dhani in Abdul Qodir Jaelani’s Tol Jogorawi accident case.In the analysis, the writer found five types of style in sentence structure scope namely: Climax, Anticlimax, Parallelism, Antithesis, and Repetition. Furthermore, the writer found five types of style in directing meaning (figurative language) scope which are Personification, Hyperbole, Synecdoche, Understatement, and Apostrophe. Types of style which are mostly used by Farhat Abbas are parallelism and repetition which are six sentences and hyperbole which are three sentences. The analysis shows that Farhat Abbas uses certain style to emphasize effect in order to make sure whether what he said is true and believable.The writer suggests that the next researchers analyze more about the stylist ics in the different object and use all of st ylist ics scope on Keraf’s theory (2010) or use other theories of stylistics.